Cyanobacterial Hydrogen Metabolism : Transcriptional Regulation of the Hydrogenases in Filamentous Strains - Axelsson, Rikard (Uppsala universitet, Fysiologisk botanik, 2003)
Cyanobacteria are a heterogeneous group of phototrophic microorganisms. Many cyanobacteria have the capacity to fix atmospheric nitrogen. During the process of nitrogen fixation, molecular hydrogen is produced. Three enzymes are directly involved in hydrogen metabolism in cyanobacteria. A nitrogenase, evolving hydrogen during nitrogen-fixation, an uptake hydrogenase, recycling the hydrogen produced by nitrogenase, and a bidirectional hydrogenase that has the capacity to both take up and produce hydrogen. The main objective in this thesis was to examine the transcriptional regulation of both the uptake and the bidirectional hydrogenase in filamentous cyanobacteria. The transcriptional regulation of the uptake hydrogenase was demonstrated to be influenced by external conditions in Nostoc muscorum and Nostoc punctiforme. Nickel, molecular hydrogen, and anaerobic conditions all induced the relative amount of uptake hydrogenase transcript. In addition, a transcript could be detected in nitrogen-fixing, but not in non-nitrogen fixing conditions. The transcriptional regulation of the bidirectional hydrogenase in N. muscorum and Anabaena PCC 7120 was also examined. The relative amount of transcript from the bidirectional hydrogenase in both strains was demonstrated to increase during anaerobic conditions. Moreover, experiments using N. muscorum demonstrated that addition of nickel also increase the amount of transcript. However, no change in the relative amount of transcript from the bidirectional hydrogenase could be observed by additional hydrogen or during a shift from non-nitrogen fixing to nitrogen fixing conditions. The genes responsible for maturation of the hydrogenase were identified, cloned and sequenced in N. punctiforme. The transcription of the genes was examined and all genes were located on a single transcript. Like the uptake hydrogenase, a transcript could be detected under nitrogen-fixing but not under non-nitrogen fixing conditions. Initial studies, using microarrays, were used to analyse and compare the transcription of a large set of Anabaena PCC 7120 genes under non-nitrogen and nitrogen-fixing conditions. Both up- and down-regulated genes could be identified. This thesis advances the knowledge about the transcriptional regulation of the hydrogenases in filamentous cyanobacteria and can be used as a platform for further experiments aiming at a modified hydrogen metabolism.